Macrocylic Picolinamide Complexes and their Catalytic Reactivity in Allylic Oxidation - Yu, Peng; Gao, Shu; Tang, Ruiren (Current Organocatalysis, 2015)
This paper describes the synthesis, characterization and catalytic activities of three closed-loop picolinamide complexes. They were prepared by Mn(II), Cu(II), Co(II) acetate and macrocylic ligand (L), which was formed by the condensation between 2,6-pyridinedicarboxylic acid chloride and 2,6-diaminopyridine. These complexes have been characterized by XRD, 1H NMR, IR, UV-vis DRS, Element analysis and TGA. Their catalytic activities in allylic oxidation of cyclohexene and isophorone with molecular oxygen as primary terminal oxidant were investigated for the first time. The influences of reaction temperature, the amount of catalyst and reaction time on the oxidation of cyclohexene by Co-L were also investigated. The results show that the Co-L can be obtained optimum catalytic efficiency, giving 58.2% conversion of cyclohexene and maximum selectivity of 83.4% for 2-cyclohexene-1-one; 15.4% conversion of isophorone and 46.2% selectivity of ketoisophorone. The heterogeneous catalysts can be easily separated for reuse at least three times without any significant change in selectivity.
Keywords: metal organic complexes